Adhesive joining of structural components : new insights and technologies - Pegoretti, Alessandro (Society of Automotive Engineers. Electronic publications., 2018)
This book introduces the reader to some recent progress involved in adhesive joining of structural components. The chapters, seminal SAE International technical papers, cover the most recent advances in adhesive materials, surface preparation and controls, innovative bonding technologies, hybrid bonded/bolted joints, non-destructive testing and failure modelling of adhesively bonded joints.